Pengaruh Kinerja Kepala Sekolah terhadap Kesejahteraan Guru dan Kemajuan Lembaga PAUD di Desa Cangkuang Kulon - Nurleni, Nurleni; Mulyaniapi, Tepi; Anwarruddin, Anwarruddin (Institut Agama Islam Persis Bandung, 2025)
This study aims to analyze the influence of early childhood education (ECE) principals’ performance on teacher well-being and institutional development in Cangkuang Kulon Village, Dayeuhkolot District, Bandung Regency. The research employed a quantitative approach with a total sampling technique involving 54 teachers from 23 ECE institutions. The research instrument consisted of a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis included validity testing, reliability testing, normality testing, and t-tests to examine the influence among variables. The results show that the performance of ECE principals in Cangkuang Kulon Village falls into the high category (74.1%). ECE teachers demonstrated a good level of well-being (64.8%), while the development of ECE institutions also fell into the high category (59.3%). However, the t-test results indicate that the principal’s performance does not have a significant effect on teacher well-being (sig. 0.322 > 0.05), but it does have a significant effect on the development of early childhood education (ECE) institutions (sig. 0.027 < 0.05). These findings suggest that improvements in principal performance primarily influence institutional aspects, such as the quality of learning services and the availability of facilities and infrastructure, but do not directly affect teacher well-being. This study underscores the importance of strengthening principals’ leadership capacity as a strategic factor in driving the advancement of ECE institutions.